Computer science for kids : a storytelling approach - Looper, Jen (John Wiley & Sons, Inc., 2023)
A kid-friendly and rigorous new way to teach young readers the fundamentals of computer science In Computer Science for Kids: A Storytelling Approach, AWS Head of Academic Advocacy and Google Developer Expert Dr. Jen Looper delivers a colorful, fun, and exciting demonstration for young readers who want to learn the basics of computer science. Using a variety of technologies, the book covers the elements of computer science in concise detail and illustrates how to build projects to learn foundational concepts behind the technology powering the internet. In the book, you'll find projects to build using both basic and emerging technologies--like SQL, game development, storytelling software, and 3D augmented reality--as well as: Chapter projects aligned to K-12 curriculum standards for grades 6-8 and a GitHub repo featuring open-source projects Lesson plans for teachers An online space for classrooms to showcase and discuss their work An easy-to-follow and kid-friendly new resource for technology-curious middle school students, Computer Science for Kids is the fun and interesting web development resource that classroom teachers, parents, and homeschooling families have been waiting for.